(untitled) (IASH Indian Journal of Arid Horticulture, 2024)
The indiscriminate use of chemical pesticides along with improper nutrient management is deleterious to the plant health, environment and human being. The quality attributes of different fruits are badly affected due to indiscriminate application of inorganic agro-chemicals which results in quality deterioration with less consumer preference and low returns to the growers. It also causes soil health deterioration and disturbs the soil microorganisms. Such practices are also common among the fruit growers. Due to these practices, the plants also become susceptible to several biotic and abiotic stresses. Therefore, it is a holistic approach based on usage of all possible sources of plant nutrients in an integrated manner is considered as alternative source to maintain soil fertility and plant nutrient supply for sustaining the desired crop productivity.